Multilateralism, Developmental Regionalism, and the African Development Bank - Nyadera, Israel Nyaburi (2022)
Promoting development in Africa has faced significant challenges partly because of the continent’s peripheral access to global markets as well as its internal geographical limitations on the movement of people, goods, and services. However, the African Development Bank (AfDB) and its “developmental” role has emerged as a practical and tailored approach to Pan-African development, especially in the midst of a growing crisis in global multilateralism. This article argues that the AfDB can be a significant promoter of African development given its unique characteristics, focus areas, and lending style that are different from other multilateral institutions. Using a case-study approach, and by analysing literature on the AfDB, policy papers, and government reports, this study explores the developmental role of the bank and demonstrates its comparative advantage to other multilateral institutions in Africa.